2021
DOI: 10.3390/en14092423
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Practical Application of Silica Nanoparticles Composite Underwater Repairing Materials

Abstract: Repairing materials are well-known to play an important role in rehabilitating and extending the service life for hydraulic concrete structures. However, current underwater repairing materials possess several problems, including insufficient bond tensile strength, inconsistency with the deformation of the old substrate, and insufficient underwater self-sealing ability. In the present paper, an experimental study was carried out to evaluate the influence of silica nanoparticles (SNs) on the properties of underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…An investigation [3,4] showed that the efect of aggregate type, water-binder ratio, and maximum aggregate size on concrete's capacity to endure abrasion was examined using the underwater technique. Te bottom slab repair concrete in the desilting channel was made using four diferent combination ratios.…”
Section: Introductionmentioning
confidence: 99%
“…An investigation [3,4] showed that the efect of aggregate type, water-binder ratio, and maximum aggregate size on concrete's capacity to endure abrasion was examined using the underwater technique. Te bottom slab repair concrete in the desilting channel was made using four diferent combination ratios.…”
Section: Introductionmentioning
confidence: 99%